Electrophysiological insights into left atrial conduction times and regional velocities in atrial fibrillation patients with and without fibrotic atrial cardiomyopathy. (3rd October 2022) - Heil, E; Gerds-Li, J H; Keznickl-Pulst, J; Furundzija, V; Hohendanner, F; Pieske, B; Schoeppenthau, D
Abstract: Background: Although considerable progress has been made in understanding the process of arrhythmogenesis in atrial fibrillation (AF) patients and the role of atrial substrate, little is known about atrial conduction characteristics in different grades of fibrotic atrial cardiomyopathy (FACM) and specific left atrial (LA) regions. Purpose: The aim of this study was to evaluate left atrial conduction times (LACT) and -velocities (CV) in electroanatomical high density maps during sinus rhythm in AF patients with and without signs of atrial fibrosis. Methods: Before radiofrequency catheter ablation electroanatomical high density mapping was performed in 41 AF patients (n=38 persistent, n=3 paroxysmal) using a 10-polar circular mapping catheter and the CARTO3 V7 navigation system (Biosense Webster, Diamond Bar, CA). We evaluated the size of low voltage areas (LVA ≤0.5mV), LACTs and local CVs at the anterior and posterior wall in low voltage areas and normal voltage areas (NVA ≥1.5mV). The latter were specifically calculated in the direction of wave-front propagation (coherent algorithm) by using 3-dimensional coordinates and local activation times of triads of sites. Results: 20 FACM and 21 non-FACM maps were analysed (1823±1031 points, n=16 low grade FACM I+II, n=4 high grade FACM III+IV, EF 57.24±6, 18%, LAVI 43.01±15, 63 ml/m 2 ). The mean total size of LVA in FACM patients was 12.06 cm 2 (anterior wall 9.51 cm 2, posterior wall 2.55 cm 2 ). LACT was 109.15±25.30 ms in our AF population, whereby LACT was shown to be longer (118.79ms, +18%) in FACM patients compared to patients without substrate (100.40 ms, p=0.01), particularly pronounced in high grade FACM (III–IV) (146 ms, +46%, p=0.001). The extension of LVA fairly strong correlated with LACT duration (Spearman ρ= 0.76). Conduction velocities in LVA revealed significantly lower (−55%) than those in NVA (0.61±0.11m/s vs. 1.34±0.30m/s, p=0.000). When comparing the anterior to the posterior wall, anterior conduction appeared slower than posterior conduction, which was significant in NVA (−12%, 1.02 vs. 1.16 m/s, p=0.0053) and failed to reach statistical significance in LVA (−11.6%, 0.61 vs. 0.069 m/s, p=0.39). See Figure 1 and Table 1 for more clinical and electrophysiological characteristics in FACM vs. non FACM patients. Conclusion: Total LACT is significantly prolonged in FACM patients and seems to correlate with LVA size. Compared to areas with a normal bipolar voltage (≥1.5mV) LVAs (≤0.5mV) show a 55% CV reduction. Furthermore, regional CVs were shown to differ between the anterior and the posterior LA wall. Those findings might have an impact on developing substrate-based ablation strategies in catheter ablation of FACM patients. Funding Acknowledgement: Type of funding sources: None.